THE CORRELATION BETWEEN STUDENTS’ MOTIVATION AND THEIR ACHIEVEMENT SCORE IN ENGLISH LEARNING AT SMP NEGERI 1 MANDE - CIANJUR - Yogi Agustin (PROJECT (Professional Journal of English Education), 2018)
The main objective of this research was to investigate the existence and the degree of the correlation between students’ motivation indexes and students’ achievement score in English learning. This research involved the first grades of SMPN 1 MANDE-Cianjur population and the sample of the research was entire (44 students) employ SPSS version 12 in investigating the correlation. The result showed that the value of r was 0,305. It means there is a  positive correlation between students’ motivation indexes and their achievement score in English learning. The correlation coefficient significant of 0,05 level. By using the coefficient of determination (CD) formula, it is known that student’s motivation indexes in learning English give 9,3% contribution to students’ achievement score in English class while the rest in influenced by other factors which are not investigated in this research